The effects of Core-polarization on inelastic form factors of 10B - Alzubadi, Ali A. (Iraqi Journal of Physics, 2012)
Inelastic transverse and longitudinal form factors of same parity havebeen studied for B 10 nucleus in the frame work of the shell model formany particles, by using He 4 as an inert core and the remainingparticles were distributed in 3 / 2 1 / 2 1p ,1p which form the modelspace. The calculations of the present work based on the harmonicoscillator potential with fixed size parameter (b). Here we use thefirst order correction for the perturbation theory and the interactionfrom Cohen-Kurath (CK). Adding the core-polarization effects toform factors calculations gave a good agreement with theexperimental data. Calculations have been performed for thetransverse excited states of: (1 ,0 )at ( E  0.178MeV )  ,.(2 ,0)at(E  3.587MeV),  (3 ,0)at(E  4.774MeV), andlongitudinal ( 2 ,1)at( E  5.164MeV )  .